2022
DOI: 10.1121/10.0013426
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark problems for transcranial ultrasound simulation: Intercomparison of compressional wave models

Abstract: Computational models of acoustic wave propagation are frequently used in transcranial ultrasound therapy, for example, to calculate the intracranial pressure field or to calculate phase delays to correct for skull distortions. To allow intercomparison between the different modeling tools and techniques used by the community, an international working group was convened to formulate a set of numerical benchmarks. Here, these benchmarks are presented, along with intercomparison results. Nine different benchmarks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…A recent study found that when using simple tissue masks with homogenized skin, bone, and brain tissue layers, multiple modeling methods, including the one used in this study, produced similar results [7] without needing any additional corrections. However, when using voxel-level properties in a viscoelastic solver, the Q factor models exclusively dissipative effects and scattering effects are introduced by the heterogeneity of the material.…”
Section: Selection Of Mapping Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…A recent study found that when using simple tissue masks with homogenized skin, bone, and brain tissue layers, multiple modeling methods, including the one used in this study, produced similar results [7] without needing any additional corrections. However, when using voxel-level properties in a viscoelastic solver, the Q factor models exclusively dissipative effects and scattering effects are introduced by the heterogeneity of the material.…”
Section: Selection Of Mapping Methodsmentioning
confidence: 64%
“…Angla et al recently presented a thorough and excellent review on this topic [6]. While several modeling approaches have been crossvalidated in simplified numerical settings [7], there are few to none open-accessible complete modeling suites that work in integration with neuronavigation systems to assist FUS-based neuromodulation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic properties of sound speed, density, alpha coefficient, and alpha power, as well as the thermal properties of thermal conductivity and heat capacity, were assigned to the skull, scalp, and brain, as reported in Table 1 (Aubry et al, 2022; Hasgall et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…We applied the MATLAB-based pseudospectral solver toolbox k-Wave [ 7 ] to perform the simulations(see Aubry et al, 2022 [ 8 ] for comparison to other comparable software). Note that K-wave itself has been extensively validated empirically [ 9 12 ].…”
Section: Methodsmentioning
confidence: 99%